Pressure-Natriuresis Response Is Diminished in Old Age - Kim, Yang Gyun; Moon, Ju-Young; Oh, Bermseok; Chin, Ho Jun; Kim, Dong Ki; Park, Jung Hwan; Shin, Sung Joon; Choi, Bum Soon; Lim, Chun Soo; Lee, Sang Ho (Frontiers in Cardiovascular Medicine, 2022)
Background: Age-related alterations in renal sodium handling affect blood pressure(BP). We aimed to clarify whether the pressure-natriuresis response changes with age, leading to BP elevation. Methods: A total of 4859 participants with normal renal function from the Korean Genome and Epidemiology Study(KoGES) and 235 patients with non-diabetic chronic kidney disease(CKD) from the ESPECIAL trial were included and divided into the younger and older groups. In ESPECIAL, participants took olmesartan from weeks 0 to 16 and were educated about a low-salt diet(LSD) from weeks 8 to 16. Results: In both studies, older participants showed lower estimated glomerular filtration rate(eGFR) and urine concentration index and higher albuminuria. In KoGES, BP was higher and urine sodium was lower in older participants. In ESPECIAL, diastolic BP at 0 week was lower in older participants. Olmesartan reduced BP in both groups, whereas LSD decreased systolic BP only in older participants. Urine sodium increased in younger participants but decreased in older participants after olmesartan use. In KoGES, urine sodium was correlated with BP in both groups after adjusting for age, sex, and eGFR; however, the correlation coefficient was lower in older participants. In ESPECIAL, only younger participants showed a significant positive association between systolic BP and urine sodium in multiple regression analysis. Conclusions: The pressure-natriuresis response was diminished in older participants with or without CKD.